Unsupervised clustering of audio data for acoustic modelling in automatic speech recognition systems - Goussard, George Willem (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2011.